Arcabouço normativo relacionado à indicação e prescrição de medicamentos fitoterápicos por farmacêuticos no Brasil - Parreira, Ana Paula Gomes; Inácia Ferreira Silva, Luana; Dewulf, Nathalie de Lourdes Souza (Cadernos ibero-americanos de direito sanitário = Cuadernos iberoamericanos de derecho sanitario, 2025)
Objective: analyze the regulatory aspects associated with pharmaceutical prescription of herbal medicines in Brazil. Methodology: an integrative review, a gray literature search and a document analysis were carried out. The databases used for the integrative review were Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature on Health Sciences and Scientific Electronic Library Online, covering the period from January/2008 to December/2023. The gray literature search was undertaken on Google Academic. The document analysis was conducted on websites of institutions relevant to the pharmaceutical practice, such as the Brazilian National Association of Magistral Pharmacists, the Brazilian Health Regulatory Agency and the Brazilian Ministry of Health. Results: few studies on the prescription of herbal medicines by pharmacists were identified, mainly concentrated in primary care. Professional insecurity was observed, associated with lack of preparation and gaps in academic training. Some studies highlighted the relevance of the pharmacist in phytotherapy, while others pointed to the absence of specific regulation. A divergence was found between the requirements established for prescription and the lack of requirements for dispensing. Official documents were identified, such as the National Policy on Integrative and Complementary Practices, the National Policy on Medicinal Plants and Phytotherapeutics, and Federal Council of Pharmacy resolutions, which provide regulatory support but are still considered insufficient. Conclusion: regulation has advanced in the integration of herbal medicines into pharmaceutical care, promoting evidence-based action for the pharmaceutical indication and prescription of herbal medicines. Submitted: 03/01/25| Revision: 09/24/25| Approved: 10/02/25 Objetivo: analizar los aspectos regulatorios asociados a la prescripción farmacéutica de fitoterápicos en Brasil. Metodología: se realizó una revisión integradora de la literatura científica y búsqueda de literatura gris, complementada con análisis documental. La revisión integradora abarcó las bases de datos Medical Literature Analysis and Retrieval System Online, Literatura Latinoamericana y del Caribe en Ciencias de la Salud y Scientific Electronic Library Online, con publicaciones entre enero/2008 y diciembre/2023. En la literatura gris las búsquedas se realizaron en Google Scholar. El análisis de documentos se realizó en sitios web de instituciones relevantes para la práctica farmacéutica, como la Agencia Nacional de Vigilancia Sanitaria, el Consejo Federal de Farmacia y el Ministerio de Salud. Resultados: se identificaron pocos estudios sobre la prescripción de fitoterápicos por parte de farmacéuticos, concentrados principalmente en la atención primaria. Se observó inseguridad profesional asociada a la falta de preparación y a vacíos en la formación académica. Parte de los trabajos registró la relevancia del farmacéutico en la fitoterapia, mientras que otros señalaron la ausencia de una reglamentación específica. Se constató una divergencia entre los requisitos establecidos para la prescripción y la inexistencia de exigencias para la dispensación. Se localizaron documentos oficiales, como la Política Nacional de Prácticas Integrativas y Complementarias, la Política Nacional de Plantas Medicinales y Fitoterapéuticos y resoluciones del Consejo Federal de Farmacia, que ofrecen respaldo normativo, aunque todavía se consideran insuficientes. Conclusión: la regulación ha avanzado en la integración de los medicamentos herbarios en la atención farmacéutica, promoviendo acciones basadas en evidencia para la indicación farmacéutica y prescripción de medicamentos herbarios. Envío: 01/03/25| Revisión: 24/09/25| Aprobación: 02/10/25 Objetivo: analisar aspectos regulatórios relacionados à indicação e prescrição farmacêutica de medicamentos fitoterápicos no Brasil. Metodologia: realizou-se uma revisão integrativa da literatura científica e busca na literatura cinzenta, complementada por análise documental. A revisão integrativa abrangeu as bases, Literatura Latino-Americana e do Caribe em Ciências da Saúde e Scientific Electronic Library Online, com publicações entre janeiro/2008 e dezembro/2023. Na literatura cinzenta, as buscas foram realizadas no Google Acadêmico. A análise documental foi realizada em sites de instituições relevantes à prática farmacêutica como a Agência Nacional de Vigilância Sanitária, Conselho Federal de Farmácia e Ministério da Saúde. Resultados: não foram identificados estudos sobre a prescrição de fitoterápicos por farmacêuticos na revisão integrativa, porém na literatura cinzenta foram encontrados dois estudos, concentrados principalmente na atenção primária. Observou-se insegurança profissional associada à falta de preparo e lacunas na formação acadêmica. Parte dos trabalhos registrou a relevância do farmacêutico na fitoterapia, enquanto outros apontaram a ausência de regulamentação específica. Constatou-se divergência entre os requisitos estabelecidos para prescrição e a inexistência de exigências para dispensação. Foram localizados documentos oficiais, como a Política Nacional de Práticas Integrativas e Complementares, a Política Nacional de Plantas Medicinais e Fitoterápicos e resoluções do Conselho Federal de Farmácia, que oferecem respaldo normativo, porém ainda considerados insuficientes. Conclusão: a regulamentação tem avançado na integração dos medicamentos fitoterápicos ao cuidado farmacêutico, promovendo a atuação baseada em evidência para a indicação e prescrição farmacêutica de medicamentos fitoterápicos. Submissão: 01/03/25| Revisão: 24/09/25| Aprovação: 02/10/25